Ten-Year Outcomes of Hip Arthroscopy for the Treatment of FAI and Labral Tears in Patients with a Workers' Compensation Claim - Domb, Benjamin G; Sikligar, Drashti; Keane, Jessica; McCarroll, Tyler R; Kahana-Rojkind, Ady H; Quesada-Jimenez, Roger (Journal of bone and joint surgery. American volume, 2025)
Workers' Compensation (WC) status has been associated with inferior outcomes in orthopaedic procedures. The purpose of this study was to determine the impact of WC on the long-term outcomes of patients undergoing hip arthroscopy for femoroacetabular impingement (FAI) and labral tears and to compare these findings with those of a propensity-matched control group. A retrospective analysis was conducted that included patients with a WC claim who underwent hip arthroscopy for FAI and labral tears between 2008 and 2013. Included patients had complete preoperative and minimum 10-year postoperative questionnaires for patient-reported outcomes (PROs) or a documented end point. Patients were propensity-matched to a control group without a WC claim in a 1:3 ratio on the basis of age at the time of surgery, sex, body mass index, acetabular Outerbridge grade, and capsular treatment. Clinically meaningful thresholds, complications, survivorship, work type, and return-to-work rates were analyzed. A total of 280 patients (WC group, 70; control group, 210) were included in the study. The WC group had a mean follow-up time of 123.9 ± 22.6 months. Compared with the matched control group, the WC group had worse preoperative PRO scores but a greater magnitude of improvement. The groups had similar (p > 0.05) rates of reaching the minimal clinically important difference (MCID) and patient acceptable symptomatic state (PASS) values for the modified Harris hip score (MCID: 93.0% [WC group], 79.2% [control group]; PASS: 83.7% [WC], 77.8% [control]), the Non-Arthritic Hip Score (MCID: 90.7% [WC], 77.8% [control]; PASS: 74.4% [WC], 63.2% [control]), and the Hip Outcome Score Sport-Specific Subscale (MCID: 87.5% [WC], 72.3% [control]; PASS: 72.7% [WC], 55.6% [control]). In the WC group, 82.9% of patients returned to work, with a mean time to return to work of 8.0 ± 7.4 months. The WC group had a higher rate of revision hip arthroscopy than the control group, with a threefold relative risk (95% confidence interval, 1.6 to 5.7; p < 0.001) and a mean time to revision of 28.3 ± 37.1 months. Hip arthroscopy for the treatment of FAI and labral tears in patients with a WC claim was associated with favorable outcomes and a high return-to-work rate at a minimum 10-year follow-up. These results were comparable with those of a benchmark control group. However, the WC group had a significantly higher rate of revision hip arthroscopy than the control group. Therapeutic Level III . See Instructions for Authors for a complete description of levels of evidence.